Autofiction A Female Francophone Aesthetic of Exile. - Wimbush, Antonia, 1989- (Contemporary French and francophone cultures., 2021)
This book examines themes of exile, mobility, and identity in contemporary autofictional narratives written in French by women writers from across the francophone world. It reads exile in light of both gender and literary genre, arguing that autofiction gives women the space to reconfigure their exile on their own terms.